2007
DOI: 10.1002/gps.1935
|View full text |Cite
|
Sign up to set email alerts
|

Do family caregivers perceive more difficulty when they look after patients with early onset dementia compared to those with late onset dementia?

Abstract: Our findings demonstrated that additional resources, such as care services, should be provided for sufferers of EOD, in order to allow family caregivers to cope with difficulties associated with patient behavioural problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
109
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(113 citation statements)
references
References 25 publications
3
109
0
1
Order By: Relevance
“…Female caregivers are more likely to be depressed 1 and burdened 2 than their male counterparts. By contrast, a care-recipient factor, younger age of dementia onset, predicts greater caregiver burden 3 and depression. 4 Central to understanding caregiver outcomes is caregiver coping 5 : the cognitive and behavioral effort to manage demand.…”
mentioning
confidence: 80%
“…Female caregivers are more likely to be depressed 1 and burdened 2 than their male counterparts. By contrast, a care-recipient factor, younger age of dementia onset, predicts greater caregiver burden 3 and depression. 4 Central to understanding caregiver outcomes is caregiver coping 5 : the cognitive and behavioral effort to manage demand.…”
mentioning
confidence: 80%
“…Both found that, despite no significant differences in cognitive functioning or behavioral disturbance, there was a significant difference between carers. Carers of younger people with dementia had significantly higher levels of burden (Freyne et al 1999) and they were also more likely to perceive difficulties due to behavioral problems (Arai et al 2007). This difference in burden may be due to carers of younger people with dementia having a longer duration of caring and less support than older carers, or to individual factors influencing carer response (Freyne et al 1999).…”
Section: Impact On the Family G E N E R A L C A R E R O U T C O M E Smentioning
confidence: 92%
“…Still, neuropsychiatric symptoms should be paid appropriate attention to in the diagnosis, treatment, support and psycho-education of YO-AD patients and caregivers, especially since previous research indicated that YOD caregivers perceive greater difficulties due to neu-ropsychiatric disturbances than do LOD caregivers [57]. Similar to LO-AD, apathy is the most important symptom to focus on in YO-AD.…”
Section: Discussionmentioning
confidence: 99%